PTPN14 regulates Roquin2 stability by tyrosine dephosphorylation. Issue 18 (17th September 2018) - Choi, Jaewoo; Saraf, Anita; Florens, Laurence; Washburn, Michael P.; Busino, Luca
ABSTRACT: Protein phosphorylation regulates a variety of cellular signaling pathways and fundamental mechanisms in cells. In this paper, we demonstrate that the mRNA decay factor Roquin2 is phosphorylated at tyrosine residue in position 691 in vivo . This phosphorylation disrupts the interaction with KLHL6, the E3 ligase for Roquin2. Furthermore, we establish that the tyrosine phosphatase PTPN14 specifically interacts with Roquin2 through its phosphatase domain and dephosphorylates Roquin2 tyrosine 691. Overexpression of PTPN14 promotes Roquin2 degradation in a KLHL6-dependant manner by promoting interaction with KLHL6. Collectively, our findings reveal that PTPN14 negatively regulates the protein stability of Roquin2, thereby adding a new layer of regulation to the KLHL6-Roquin2 axis.